Modelagem em painel dinâmico dos determinantes populacionais de corrupção nos estados brasileiros - Oliveira, Wilma Marques de (2017)
The objective of this study is to investigate whether, as variables, real GDP, population, average years of schooling, proportion of poor households and Gini index are significant to explain the level of corruption measured by the Government Corruption Indicator (ICG) in the 27 (twenty-seven) units of the Brazilian federation. First, review some important theoretical and empirical works that address an economic view of corruption. Then, it proposes a parsimonious and well specified modeling to identify, through a dynamic balance panel during the period of 1998 to 2008, an influence of the explanatory variables on the result of the ICG obtained for each unit of the Brazilian federation. Second, as estimates of the framework, an increase in the ICG in the previous year implies reducing the indicator no later year. In addition, a negative correlation presented by average variable of years of study suggested that can be promoted for a reduction of corruption. What is the difference and concentration of income, the result of the estimation, is the income measure, the result of the estimation, as the less rich and unequal units of the federation practice less corrupt acts, which is configured as socially desirable. The relevance of the study is developed in the absence of studies investigating the determinants of corruption at the regional level, which is an indicator of the measurement of corrupt acts.